Analisis Pengaruh Selfie pada Proses Pengambilan Keputusan Pelanggan Berbasis Aisas - Sa'ban, Faisal; Asakdiyah, Salamatun; Setiawan, Zunan; Adhilla, Fitroh; Siswanto, Agus (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study examines and analyzes the effect of the selfie promotion method on the customer's decision-making process using the AISAS model. Data were assessed and analyzed using PLS-SEM modeling. The results show that the AISAS model with selfie promotion produces better in-sample predictions (model selection criteria). This study is important to understand the effect of advertising-supported selfie promotion on decision-making processes and provide insight into how companies can leverage advances in communication technology to drive selfie-driven behavior promoting innovative and competitive products. Assessment of the effect of selfie promotional advertisements on the decision-making process using PLS-SEM and model selection criteria for articulating the relevance of selfies as a promotional tool.